FATAMORGANA ISLAMSKE UMJETNOSTI: RAZMIŠLJANJA O PROUČAVANJU JEDNE OPSEŽNE OBLASTI (II) - Blair, Sheila S.; Bloom, Jonathan M.; Abadžić-Hodžić, Aida (Novi Muallim, 2009)
(The mirage of Islamic art: reflections on the study of an unwieldy field, Art Bulletin, 00043079, Vol. 85, College Art Association of America, 2003) Prijevod s engleskog: Aida Abadžić-Hodžić